Assessment requirements for adequate knowledge management, case study in an organizational unit's operational support of a financial institution (2019)
For many authors, the study from the viewpoint of resources gives organizations the strategic importance because of its intangible attributes, such that the analysis of assets based on information and knowledge, is of special interest as a source of competitive advantage. Thus, research aimed at evaluating the organizational and technological requirements that encourage knowledge sharing intention, this activity being vital in the process of knowledge sharing, in light of the findings in the scientific literature. Thus, firstly, a diagnosis was made by the method of the Partial Least Squares Regression (PLS), to consider the impact of organizational factors on intention to share knowledge. Secondly, we have identified organizational and technological requirements expected to assess and prioritize under the stamp of quality methodical trial provided by the Quality Function Deployment model. At the organizational field, the case study indicates that employees expect their associated actions to facilitate the sharing of knowledge are well recognized, and in the technological field indicates that collaborative tools present in the organizational unit to support operations a financial institution in Colombia, meets the three technological requirements identified most impact on the quality of knowledge management, which are, in order of efficiency, usability and functionality.